2022
DOI: 10.3390/toxins14010035
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Detrusor OnabotulinumtoxinA Injections and Conversion to Other Bladder Management in Patients with Chronic Spinal Cord Injury

Abstract: This study investigated the satisfaction with continued detrusor Botox injections for urinary incontinence and conversion to other surgical procedures and bladder management procedures for neurogenic detrusor overactivity (NDO) in patients with chronic spinal cord injury (SCI). A total of 223 patients with chronic SCI underwent detrusor Botox 200U for urodynamically confirmed NDO and urinary incontinence. After initial detrusor Botox injections, patients opted to either continue detrusor Botox injections every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Our study is the first to report the impact of spinal pathology on post-SNM BoNTA. In prior reports of BoNTA in SCI patients, the success rates were 64.2%, 28 compared to 50%-91% in patients with stroke 29,30 and 79.2%-100% in patients with Parkinson's disease. 31,32 A large phase three trial reported similar results in patients with SCI and MS, 21 with the success rate around 75%.…”
Section: Discussionmentioning
confidence: 91%
“…Our study is the first to report the impact of spinal pathology on post-SNM BoNTA. In prior reports of BoNTA in SCI patients, the success rates were 64.2%, 28 compared to 50%-91% in patients with stroke 29,30 and 79.2%-100% in patients with Parkinson's disease. 31,32 A large phase three trial reported similar results in patients with SCI and MS, 21 with the success rate around 75%.…”
Section: Discussionmentioning
confidence: 91%
“…BoNT-A was initially introduced in urology for treating patients with neurogenic lower urinary tract dysfunction (NLUTD) due to chronic SCI [13,14]. Detrusor BoNT-A injection reduces the incidence of NDO and lowers intravesical pressure, which improves urinary incontinence [15][16][17]. Subsequent studies proved the efficacy of BoNT-A on autonomic dysreflexia (AD) in patients with high-level SCI, in addition to treating NDO and urinary incontinence in pediatric patients with myelomeningocele or other NLUTDs [6].…”
Section: Bont-a Detrusor Injection For Neurogenic Detrusor Overactivi...mentioning
confidence: 99%
“…The most common cause of discontinuation is treatment failure (43.7%). In a long-term follow-up study of the satisfaction rate of patients with SCI and NDO who received detrusor Botox injections, only 48.4% of patients continued Botox injections over 7 years [ 61 ]. The presence of high detrusor pressure and higher-grade bladder outlet resistance are predictive of a decrease in incontinence.…”
Section: Clinical Application Of Botox On Ndo: Efficacy Adherence Adv...mentioning
confidence: 99%